Reclaiming truth in the post-truth era: a philosophical perspective on Bakhtin’s dialogism and discourse production - Amin, Chair; Jamil, Achmad; Briandana, Rizki (International Journal of Communication and Society, 2025)
This study explores the epistemic and ethical disruptions of public communication in the post-truth era through the theoretical lens of Mikhail Bakhtin’s dialogism. In an age where emotions, ideological narratives, and algorithmic amplification dominate digital discourse, truth has become a contested and manipulable construct rather than a product of dialogic exchange. Using a qualitative-descriptive approach, this research analyzes various forms of public digital content, such as online news, political memes, and viral hashtags, through critical discourse analysis and Bakhtinian concepts of heteroglossia, polyphony, and answerability. The findings reveal three key phenomena: the abandonment of dialogically-constructed truth, the fragmentation of digital heteroglossia into polarizing ideological bubbles, and the erosion of dialogic ethics manifested in the collapse of answerability. These trends mark a shift from inclusive public dialogue toward monologic affirmation and symbolic confrontation.Despite these challenges, the study identifies dialogism’s normative and pedagogical potential for rebuilding ethical communication in fragmented societies. Dialogism-based critical media literacy encourages reflective listening, ideological awareness, and multi-voiced engagement, providing a transformative strategy to counter disinformation and reclaim democratic discourse. This research offers both theoretical and practical contributions by positioning dialogism not only as an analytical tool, but also as an ethical foundation for inclusive, reflexive, and responsible communication in the digital age.